Landscape, Soil, and Plant Analysis of Japanese Stiltgrass (Microstegium vimineum) Invasion in the Piedmont Region, SC. Issue 9 (15th May 2017) - Mikhailova, Elena A.; Hagan, Donald; Sharp, Julia; Ritter, Brian; Stiglitz, Roxanne; Mealing, Veeander; Allerton, Tristan; Burdette, Kylie; Solomons, Allen; Schlautman, Mark A.
ABSTRACT: Japanese stiltgrass ( Microstegium vimineum ), an exotic invasive plant, is native to Southeast Asia. This study was conducted to determine the chemical composition of Japanese stiltgrass as well as soil and landscape characteristics that correlate with invasion of Japanese stiltgrass around Lake Issaqueena in the upper Piedmont of South Carolina. Geographic Information Systems (GISs) and Light Detection and Ranging (LiDAR) were used to determine the spatial pattern of invasion with respect to the aspect, slope, canopy cover, soils, and distance to roads and trails. Japanese stiltgrass was distributed on both sides of Lake Issaqueena in Pacolet and Madison soil map units (Fine, kaolinitic, thermic Typic Kanhapludults) on the average slopes of 21%, but it was particularly common on the eastern shore of the lake in low-lying wet and shaded areas (mean canopy cover 51%). In addition, invasion by Japanese stiltgrass was correlated with the proximity to roads and trails. Plant tissue analysis revealed many differences in the distribution of macronutrients, macrominerals, and micronutrients in the leaves, stems, and roots of Japanese stiltgrass, although those differences were not always statistically significant. Concentrations of nitrogen (N), phosphorus (P), and calcium (Ca) were the highest in leaves while zinc (Zn) concentrations were the highest in stems and concentrations of magnesium (Mg), copper (Cu), manganese (Mn), iron (Fe), and sodium (Na) tended to be higher in roots. Carbon (C), sulfur (S), and potassium (K) concentrations were generally higher in above-ground tissues versus roots. Soil chemical analysis revealed no statistical differences between control and invaded plots. Our findings suggest that watershed areas surrounding lakes may be particularly susceptible to the invasion of Japanese stiltgrass due to their microclimates, low-lying wet pathways for seed distribution and recreational uses.